A Pilot Study of Olfactory Training in Older Hyposmic Adults. Issue 6 (November 2019) - Lamira, Jensine M.; Soler, Zachary M.; Schlosser, Rodney J.
Background: Olfactory loss is a common problem that significantly impacts quality of life. Olfactory training (OT) has been used most commonly for viral and traumatic olfactory dysfunction (OD) in younger subjects with hopes of neural regeneration, improved olfactory function, and subjective well-being. The objective of this study was to investigate the impact of a novel form of OT using 12 odors in participants over 45 years of age with objective OD. Methods: Twenty-nine participants underwent OT using 12 standardized odor pens for a duration of 6 months. Objective OT of Threshold, Discrimination, and Identification and patient-reported outcomes were assessed at baseline and after 6 months of OT. Results: Of the 29 participants who entered the protocol, only 16 subjects completed all 6 months of OT. Significant improvements were seen in overall Threshold Discrimination Identification (TDI; mean 4.40 points, P  = .007), Discrimination (mean 1.44 points, P  = .019), and Identification (mean 2.02 points, P  = .011). Forty-four percent of subjects who completed OT achieved a mean clinically important difference of at least 5.5 points on TDI. Conclusion: There was no significant change in patient-reported outcome measures, and no baseline factors were associated with change in olfaction. In this study, OT with 12 odors improves objective olfaction in nearly half of the older adults with OD. Further investigation is necessary to determine the impact of improved olfaction on overall health outcomes.